A Practical Guide to Prairie Reconstruction : Second Edition - Kurtz, Carl (Book collections on Project MUSE., 2013)
Thirty-five years and many acres after planting his first patch of prairie flowers, the author is considered one of the deans of the great tallgrass prairie revival. The Prairie Enthusiast called the 2001 edition of his book a "readable and understandable introduction to prairie and the general steps in carrying out a reconstruction." This second edition reflects his increased experience with reconstructing and restoring prairie grasslands. The author has completely revised every chapter of the first edition, from site selection and harvest to soil preparation, seeding, postplanting mowing, burning, and growth and development. He has also written additional chapters on establishing prairie in old pastureland and on the judicious use of herbicides, including a table that shows particular problem species, the types of herbicides that are most effective at controlling them, and the timing and method of treatment.